An Effective Data Privacy Mechanism through Secure Session Key Exchange Model for MANET - K. Ramesh Rao; S.N. Tirumala Rao; P. Chenna Reddy (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Data privacy in the mobile ad-hoc network is a problem due to wireless medium, frequent node movement and lack of any centralized infrastructure support. In such case, it is very important to build a reliable and secure network and achieve high throughput in MANET. The reliability and security of a network depend on whether the network remains linked to different failures and malicious activities, which is the fundamental issue that needs to be focused when designing a secure routing protocol in MANET. This paper proposes an effective privacy mechanism to handle data security through a novel secure session key exchange model, which provides the node data privacy and network stability for a longer period of time and prevents abnormal behavior changes due to malicious behavior and different type of attacks in the network. The simulation results show improvement in throughput with nominal overhead and end-to-end delay in different malicious conditions against existing protocols.